Abscopal effect triggered by radiation sequential mono-immunotherapy resulted in a complete remission of PMMR sigmoid colon cancer - Zhou, Pu; Wang, Yan; Qin, Si; Han, Yan; Yang, Yumeng; Zhao, Liang; Zhou, Quan; Zhuo, Wenlei (Frontiers in Immunology, 2023)
Background Radiation therapy combined with immune checkpoint inhibitors (ICIs) has recently turned into an appealing and promising approach to enhance the anti-tumor immunity and efficacy of immunological drugs in many tumors. Abscopal effect induced by radiation is a phenomenon that often leads to an efficient immunity response. In this study, we investigated whether the combination of the immunogenic effects derived from radiotherapy sequential ICIs-based therapy could increase the incidence of abscopal effects, and improve the survival rates. Case presentation We described a clinical case regarding a 35-year-old male patient who was admitted to our hospital with a diagnosis of adenocarcinoma of the sigmoid colon and synchronous multiple liver metastases following a surgical resection. The molecular pathological examination showed immune-desert phenotype and proficient mismatch repair (pMMR). The patient was treated with adjuvant chemotherapy after surgery, however, after 7 months, multiple metastasis in the pelvic lymph nodes were diagnosed. Unfortunately, the tumor progressed despite multiple cycles of chemotherapy combined with cetuximab or bevacizumab. Within the follow-up treatment, the patient was administered with only 50Gy/25F of radiation dose to treat the anastomotic lesions. Subsequently, mono-sindilizumab was used as systemic therapy, leading to a rapid reduction of all pelvic lesions and complete clinical remission. So far, the patient survived for more than 20 months under continuous mono-sindilizumab treatment and is still in complete remission. Conclusion A localized radiotherapy combined with a sindilizumab-based systemic therapy may overcome the immune resistance of pMMR metastatic colorectal cancer (mCRC), thus obtaining greater efficacy of the therapy. Its mechanism may be related to the abscopal effect obtained by the synergistic use of radiation and sindilizumab, which should be further investigated in the future.